Observaciones lingüísticas de Kavafis a la Gramática de Huber Pernot - Clair, Christos (Byzantion Nea Hellás, 2015)
The author examines a Kavafis’ commentary on Pernot’s THE GRAMMAR OF THE MODERN GREEK, which stayed as a manuscript until 1963. The author highlights the poet’s objectivity in his approach to the Greek language’s phenomena. This objective and respectful criterion towards the use and diversity on the part of Kavafis is remarkable - - considering the time in which the commentary was written and the linguistic problem in Greece. At that time, modem linguistics was hardly doing its firsts steps and spreading its postulates. On the other hand, the strong "archaizing" greek tradition had produced deep prejudices. Kavafis not only admitted the more frequent and common use, but also duality and plurality of uses. It is also remarkable that the poet admitted the aesthetic criterion before the variety of forms in use. It’s worth to say that the aesthetic criterion is nowadays taken into account by socio-linguistic researchs. Kavafis did not totally condemn the use of foreign words. On the contrary, he admitted them when there is not a Greek word for a concept or object, or when there is not possibility of creating a new word. Finally, the author values Kavafis’ vast knowlwdge about the Neogreek linguistic bibliography.